2011
DOI: 10.4103/0019-509x.82873
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab plus radiotherapy in patients with unresectable locally advanced squamous cell carcinoma of head and neck region - A open labelled single arm phase II study

Abstract: Cetuximab concurrent with radiotherapy is a safe and effective option in advanced head-neck cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
4
12
0
Order By: Relevance
“…Thus, radiotherapy combined with cetuximab can be seen as alternative treatment option for specific cases but seems not superior to standard radiochemotherapy [33,34,35]. Some studies showed moderate improvements of local control and long-term survival after treatment with cetuximab plus radiotherapy [36,37]. Results of triple combination in randomized trials have preliminarily been reported and do also not support superiority over radiochemotherapy [38,39].…”
Section: Cetuximab Combined With Radiotherapymentioning
confidence: 99%
“…Thus, radiotherapy combined with cetuximab can be seen as alternative treatment option for specific cases but seems not superior to standard radiochemotherapy [33,34,35]. Some studies showed moderate improvements of local control and long-term survival after treatment with cetuximab plus radiotherapy [36,37]. Results of triple combination in randomized trials have preliminarily been reported and do also not support superiority over radiochemotherapy [38,39].…”
Section: Cetuximab Combined With Radiotherapymentioning
confidence: 99%
“…Dattatreya and Goswami [12] observed an overall response rate (ORR) of 68.42% and a 2-year OS of 84% in 19 unresectable patients treated with BRT, as in Bonner et al's trial [9]. At 2 years, 13 patients remained without progression.…”
Section: Resultsmentioning
confidence: 97%
“…By the time the study was published, concomitant CTRT had become the standard of care for unresectable HNSCC. Dattatreya, et al 6 recorded 19 unresectable patients treated with CTX/RT, with Bonner's scheme, and observed overall responses (OR) of 68.42% and two-year OS of 84%. Two years after the protocol was concluded, 13 patients remained free of progression.…”
Section: Discussionmentioning
confidence: 99%